Interleukin (IL)-21 and IL-21 receptor expression in peripheral T and B cells of patients with breast cancer: IL-21 and IL-21R in breast cancer - Babaeinia, Elham; Ghods, Atri; Rasolmali, Reza; Talei, Abodol-Rasoul; Mehdipour, Fereshteh; Ghaderi, Abbas (Cellular and Molecular Biology, 2024)
IL-21 is a cytokine with versatile antitumor and pro-tumorigenic activities. It is mainly produced by CD4+ T cells and B cells are one of its pivotal targets. In this study, we assessed and compared the expression of IL-21 by CD4+ T cells and the IL-21 receptor (IL-21R) on B cells in the peripheral blood of women with breast cancer and healthy individuals. Blood samples were taken from both patients and controls. Mononuclear cells were seperated using Ficoll-Hypaque density gradient centrifugation. These isolated cells were then stained with either anti-CD19/anti-IL-21R or anti-CD4/anti-IL-21 antibodies and analyzed using flow cytometry. The results showed that there was no significant difference in the percentage of IL-21R+ B cells and IL-21+CD4+ T cells between patients and controls. However, the percentage of CD4+ T cells decreased significantly in patients with breast cancer (P=0.003). This decline was observed from the early stage and before lymph node (LN) involvement. In comparison to the control group, IL-21R+ B cells were relatively lower in patients with stages I+II and those with fewer than 4 involved LNs. The intensity of IL-21 expression in T cells was associated with HER2 expression (P=0.029). Furthermore, we found that the majority of IL-21R+ B cells exhibited a naïve phenotype and most of IL-21+CD4+ T cells did not produce IFN-γ or IL-17. In conclusion, breast cancer from the early stages leads to a significant reduction in the proportion of peripheral CD4+ T cells. However, we did not find a significant change in IL-21 and its receptor expression during disease progression.